2022
DOI: 10.1111/corg.12483
|View full text |Cite
|
Sign up to set email alerts
|

Board surname sharing and investment efficiency: Evidence from Chinese state‐owned enterprises

Abstract: Research Question/Issue Using data on Chinese listed state‐owned enterprises (SOEs), this study examines the impact of board surname sharing on firms' investment efficiency. Research Findings/Insights We find that surname sharing among a firm's board of directors is positively associated with its investment efficiency. The main result continues to hold when using alternative measures and accounting for endogeneity. Specifically, we show higher surname homogeneity mitigates agency costs and information asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…In the director’s context, the SCAT implies how directors socialize into the boardrooms by grouping themselves with a person who shares similar values or characteristics. The categorization also helps the directors provide a sense of belonging in the boardrooms such as minority directors such as female or non-citizen directors (Chen et al, 2016; Jonsdottir et al, 2015; Kaczmarek et al, 2012a); shorten their social distance such as sharing a similar surname and or being members of the corporate elite (Huang et al, 2022; McDonald & Westphal, 2010; Pirzada et al, 2017; Zhang et al, 2020); implied their perceived role, such as being an expert or typical director, family or lone-founder director, and first or non-first son director (Cannella et al, 2015; Elms & Nicholson, 2020; Yoo et al, 2014); and elected union directors (Guerrero et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the director’s context, the SCAT implies how directors socialize into the boardrooms by grouping themselves with a person who shares similar values or characteristics. The categorization also helps the directors provide a sense of belonging in the boardrooms such as minority directors such as female or non-citizen directors (Chen et al, 2016; Jonsdottir et al, 2015; Kaczmarek et al, 2012a); shorten their social distance such as sharing a similar surname and or being members of the corporate elite (Huang et al, 2022; McDonald & Westphal, 2010; Pirzada et al, 2017; Zhang et al, 2020); implied their perceived role, such as being an expert or typical director, family or lone-founder director, and first or non-first son director (Cannella et al, 2015; Elms & Nicholson, 2020; Yoo et al, 2014); and elected union directors (Guerrero et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The recent study by Huang et al (2022) revealed new perspectives that identification with the role of director among board members with similar Chinese surnames improves information sharing, which helps them in decision making and leads to improved investment efficiency. The results offer new approaches, since most of the previous literatures come to opposite conclusions.…”
Section: Identifications To Multiple Identities and Social Groups Of ...mentioning
confidence: 99%
“…This article focuses on the Chinese stock market A-share companies that are owned by private investors, as the operation and management of state-owned enterprises (SOE) are subject to administrative orders rather than monetary incentives. Zhang (2002) points out that maximizing shareholders’ value or firm value is not the primary goal for the management of SOEs. Yan and Deng (2018) show that the regulated remuneration of the CEOs of SOEs cannot significantly reduce innovation activities, meaning that SOE managers have no incentive to behave myopically for bonuses.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…In China, surnames are formed after an individual is born and often accompany them throughout their lives because surnames are a symbol of dignity and the key to identifying ancestors (Zhang et al, 2020). As a series of studies have shown, individuals socially categorize themselves and others into social groups based on visible or easily observable characteristics (e.g., surname) (Du, 2019), and people with the same surname tend to consciously or unconsciously group themselves into an identical social group (e.g., belonging to the same clan) (Huang et al, 2022). As a result, the social distance between individuals is reduced and positive prejudice or favoritism toward each other is created (Du, 2019; Tan et al, 2021; Xu et al, 2022).…”
Section: Hypotheses Developmentmentioning
confidence: 99%